2003
DOI: 10.1093/hmg/ddg284
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in COX10 result in a defect in mitochondrial heme A biosynthesis and account for multiple, early-onset clinical phenotypes associated with isolated COX deficiency

Abstract: Deficiencies in the activity of cytochrome c oxidase (COX) are an important cause of autosomal recessive respiratory chain disorders. Patients with isolated COX deficiency are clinically and genetically heterogeneous, and mutations in several different assembly factors have been found to cause specific clinical phenotypes. Two of the most common clinical presentations, Leigh Syndrome and hypertrophic cardiomyopathy, have so far only been associated with mutations in SURF1 or SCO2 and COX15, respectively. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(162 citation statements)
references
References 47 publications
4
158
0
Order By: Relevance
“…Interestingly, these analyses also showed hCOA3 interacts with some complex I subunits such as NDUFA9 and NDUFV1 but not others such as NDUFS1. It has been recently reported that complex I assembly takes place in the context of supercomplexes or respirasomes (26), which could explain the interaction between COX and complex I assembly intermediates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these analyses also showed hCOA3 interacts with some complex I subunits such as NDUFA9 and NDUFV1 but not others such as NDUFS1. It has been recently reported that complex I assembly takes place in the context of supercomplexes or respirasomes (26), which could explain the interaction between COX and complex I assembly intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of COX2 and COX3 and their stability over a 7-h chase were as in wild-type cells. Although these subunits have a longer half-life than COX1, they are known to be unstable when COX assembly is compromised (26,35), and, accordingly, their steady-state levels in hCOA3 interfered cells were lowered markedly.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture is often not helpful in directing the genetic analysis, because there is a significant overlap between phenotypes associated with specific gene defects (for example, hypertrophic cardiomyopathy is a feature of SCO2, COX10 and COX15 mutations 2 ), and because of the phenotypic variability of mutations in individual genes, such as COX10 15 and COX15. 16 Moreover, SURF1 defects, which are usually associated with LS, may also present with different clinical phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Microcellmediated chromosome transfer has been used successfully for identifying specific gene defects, 19 but it is a complex and manpowerintensive procedure and is not suitable for analyzing large cohorts of patients. Simpler methods have been developed on the basis of functional complementation of cultured fibroblasts using specific lentiviral vectors; 15 however, for most of our patients, the muscle biopsy fragment was the only biological material available for our study. Therefore, we stress the importance of collecting skin fibroblasts in all patients in whom a respiratory chain defect is suspected.…”
Section: Resultsmentioning
confidence: 99%
“…A homozygous mutation in COX6BI, identified in brothers from a consanguineous Saudi Arabian family, presented with gait instabilities visual disturbances, progressive neurological deterioration and leukodystrophic brain changes. 122 Mutations in COX10, a homologue of yeast haem A:farneslytransferase, are associated with Leigh syndrome 123,124 and a multisystem disorder. 123 Atypically, mutations in COX7B 125 are associated with facial dysmorphisms and congenital abnormalities, 126 and a single mutation in the structural subunit gene, COX4I2, was identified in adult Arab Muslim patients with exocrine pancreatic insufficiency, dyserythropoietic anaemia and calvarial hyperostosis.…”
Section: Disorders Resulting From a Reduction In Mtdna Stabilitymentioning
confidence: 99%